Analysis of the Teacher's Preparation for the Lesson (In the Case of Foreign Languages) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article provides information about the importance of preparation for the lesson in the formation of the teacher's pedagogical skills, and the methodical measures to be taken to prepare for the lesson. Analysis of educational language material Each lesson or group of lessons (paragraph) contains a specific language material. It is not unlikely that the new material will present some degree of difficulty. We determine this by conducting a linguistic unit from the practice of students' language experience.